Implementation of total laparoscopic hysterectomy as day case surgery - Alistair Ward; Samantha Roberts; Naomi Harvey; Emily Dana; Charlotte Goumalatsou; Melanie Tipples (BMJ Open Quality)
Elective surgeries within the National Health Service are frequently cancelled due to shortages of inpatient beds due to acute emergency admissions, and more recently, the COVID-19 pandemic. The aim of this quality improvement project was to initiate a day case hysterectomy pathway, prospectively collecting data on a group of selected motivated patients to assess its feasibility and safety. Interventions to maximise the chance of same day discharge included preoperative education and hydration, alterations in anaesthetic and surgical techniques and collaborative working between surgeons and recovery nurses to safely discharge patients. In change cycle 1, 93% of patients were discharged on the same day as surgery. In change cycle 2, 100% of patients were discharged on the same day as surgery. In a patient questionnaire, 90% of patients would recommend a day case hysterectomy to their friends or family. Day case hysterectomy was safely introduced to our unit, through leaders actively encouraging contributions and feedback throughout the initiation of the pathway from different components of the multidisciplinary team, from conception to roll out of the guideline for use by other gynaecological surgical teams within the trust.